Method for improving interface performance of steel fiber and matrix in UHPC (Ultra High Performance Concrete)

By dezincifying and chelating modification treatments on steel fibers, the problem of poor interface bonding performance between steel fibers and concrete matrix in the existing technology is solved, and an efficient, economical and environmentally friendly interface bonding effect is achieved, which is suitable for UHPC large-scale application.

CN119349912APending Publication Date: 2025-01-24GUANGXI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411477851.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art has problems such as complex operation, high cost, high risk and environmental pollution in improving the interface bonding performance of steel fibers and concrete substrates, and it is difficult to be suitable for large-scale applications.

Method used

By soaking copper -plated steel fiber or stainless steel steel fiber in an alkaline solution for decaptery treatment, and chelating the electrolyte solution containing chelated agents to improve the roughness and adhesion performance of the steel fiber surface.

Benefits of technology

The efficient bonding of steel fiber and concrete substrate interface is realized, and UHPC's tensile, bending strength, and fracture toughness are improved. At the same time, it is simple, low in cost, and no environmental protection. It is suitable for large -scale applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349912A_ABST
    Figure CN119349912A_ABST
Patent Text Reader

Abstract

The invention provides a method for improving the interface performance of steel fibers and a matrix in UHPC (Ultra High Performance Concrete), and belongs to the technical field of building materials. The method provided by the invention comprises the following steps: 1, soaking copper-plated steel fibers in an alkaline solution for dezincification treatment, and then sequentially cleaning and drying the dezincified copper-plated steel fibers to obtain dezincified steel fibers; method 2: soaking the dezincified steel fiber in the method 1 in an electrolyte solution containing a chelating agent for chelating modification; the method 3 comprises the following steps: soaking the stainless steel fiber in an electrolyte solution containing a chelating agent for chelating modification; the alkaline solution is a calcium hydroxide solution, a sodium hydroxide solution or a potassium hydroxide solution; the chelating agent is ethylene diamine tetraacetic acid disodium salt. According to the method provided by the invention, the surface roughness of the steel fibers is effectively improved, and the interface bonding performance between the steel fibers and a concrete matrix is improved, so that the tensile strength, the bending strength and the fracture toughness of the prepared UHPC are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of building materials, and in particular to a method for improving the interface performance between steel fiber and matrix in UHPC. Background Art

[0002] Fiber concrete is a commonly used concrete in the field of infrastructure construction, and steel fiber concrete is one of the most commonly used types of concrete. Compared with ordinary concrete (referring to concrete without toughening fibers), steel fiber concrete has the characteristics of high tensile strength and high fracture toughness, which is due to the interfacial bonding performance between steel fibers and the concrete matrix (the bridging effect of steel fibers). At present, the most widely used steel fibers are straight steel fibers, but due to the water bleeding effect on the fiber surface, the bonding performance between steel fibers and the concrete matrix is ​​not ideal, and steel fibers are often pulled out under pull-out loads far less than their tensile strength. For this reason, it is necessary to modify the surface of steel fibers to enhance the interfacial bonding performance between steel fibers and the concrete matrix, while improving the utilization rate of steel fibers and further improving the tensile strength, bending strength and fracture toughness of steel fiber concrete.

[0003] At present, the commonly used surface treatment methods for steel fibers are mainly coating, physical grinding and chemical corrosion. The coating method includes nano-silicon dioxide coating, nano-calcium carbonate coating, silane coupling agent coating and zinc phosphate coating; the physical grinding method includes sandpaper grinding; the chemical corrosion method includes rust modification, pickling, chelation modification and the like. The above methods have improved the interfacial bonding performance between steel fibers and concrete matrix to varying degrees, but they still have their own technical defects: (1) The coating method has obvious treatment effect and can significantly improve the interfacial bonding performance between steel fibers and concrete, but the silane coupling agent coating, nano-silicon dioxide coating and existing calcium carbonate coating all have too complicated processes and high modification costs, and cannot be applied to large-scale steel fiber processing and preparation. (2) The physical grinding method is simple and efficient, but the current research is limited to the single longitudinal and transverse grinding of steel fibers. The improvement effect of random grinding is still unclear, and there is currently a lack of professional steel fiber grinding equipment. (3) Chemical corrosion is simple to operate and has obvious effects, but excessive corrosion will lead to a decrease in the ultimate strength of the steel fiber itself. In addition, it is highly dangerous during the preparation process and the residual waste pollutes the environment, making it difficult to apply on a large scale. Therefore, there is an urgent need for a steel fiber surface modification technology that is simple to operate, has outstanding effects, is economical, and can be applied on a large scale. Summary of the invention

[0004] In view of this, an object of the present invention is to provide a method for improving the interface performance between steel fiber and matrix in UHPC.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] A method for improving the interface performance between steel fiber and matrix in UHPC, comprising three methods;

[0007] Method 1: soaking the copper-plated steel fiber in an alkaline solution for dezincification treatment, and then washing and drying the copper-plated steel fiber after the dezincification treatment in sequence to obtain the dezincified steel fiber;

[0008] Method 2: soaking the dezincified steel fiber described in method 1 in an electrolyte solution containing a chelating agent for chelation modification;

[0009] Method 3: Soak the stainless steel fiber in an electrolyte solution containing a chelating agent for chelation modification;

[0010] The alkaline solution is a calcium hydroxide solution, a sodium hydroxide solution or a potassium hydroxide solution;

[0011] The chelating agent is disodium ethylenediaminetetraacetate.

[0012] In some embodiments of the present invention, the concentrations of the sodium hydroxide solution and the potassium hydroxide solution are both 0.05-0.1 mol / L, and the calcium hydroxide solution is prepared by mixing calcium hydroxide and water in a mass ratio of (0.5-2):100.

[0013] In the present invention, considering that calcium hydroxide has low cost and is easily available, the alkaline solution is preferably prepared by mixing calcium hydroxide and water in a mass ratio of (0.5-2):100 (further preferably, 1:100).

[0014] In the present invention, when the amount of calcium hydroxide is low, the speed of the dezincification corrosion reaction will decrease and the reaction time will be prolonged. When too much calcium hydroxide is added, undissolved calcium hydroxide will be deposited on the surface of the steel fiber, which will have a deteriorating effect on its interfacial properties. Therefore, the mass ratio of calcium hydroxide to water in the present invention is the best when it is within the above parameter range.

[0015] In some embodiments of the present invention, the dimensions of the copper-plated steel fiber and the stainless steel fiber are: length 20-25 mm, diameter 0.2-0.3 mm, aspect ratio 83.3-100, and tensile strength 2200-2580 MPa.

[0016] In some embodiments of the present invention, the dimensions of the copper-plated steel fiber and the stainless steel fiber are: length 20 mm, diameter 0.2 mm, aspect ratio 100, tensile strength 2580 MPa; or the dimensions are: length 25 mm, diameter 0.3 mm, aspect ratio 83.3, tensile strength 2200 MPa.

[0017] In some embodiments of the present invention, the mass ratio of the copper-plated steel fiber to the alkaline solution is 1:(30-100), preferably 1:50; the mass ratio of the dezincified steel fiber to the electrolyte solution containing a chelating agent is 1:(10-50), preferably 1:20; the mass ratio of the stainless steel fiber to the electrolyte solution containing a chelating agent is 1:(10-50), preferably 1:20.

[0018] In the present invention, when the mass ratio of the copper-plated steel fiber to the alkaline solution is too high (i.e., the amount of the copper-plated steel fiber is increased), the corrosion time required for the corrosion of the copper-plated steel fiber will be extended. When the mass ratio of the copper-plated steel fiber to the alkaline solution is too low (i.e., the amount of the copper-plated steel fiber is reduced), the corrosion rate will increase, but the number of copper-plated steel fibers processed in a single batch will be reduced. The reasons for setting the mass ratio of the stainless steel fiber to the electrolyte solution containing the chelating agent are similar to the above reasons.

[0019] In the present invention, if the mass ratio of the dezincified steel fiber to the electrolyte solution containing the chelating agent is too high, the reaction rate will decrease, and if it is too low, it will cause waste and increase the cost.

[0020] In some embodiments of the present invention, when the copper-plated steel fiber is immersed in an alkaline solution for dezincification treatment, the immersion time is 5-10 days, preferably 7 days; when the dezincified steel fiber is immersed in an electrolyte solution containing a chelating agent for chelation modification, the immersion time is 3-9 hours, preferably 3h, 6h or 9h; when the stainless steel fiber is immersed in an electrolyte solution containing a chelating agent for chelation modification, the immersion time is 3-9 hours.

[0021] In some embodiments of the present invention, when the copper-plated steel fiber is immersed in an alkaline solution, the stacking thickness of the copper-plated steel fiber is less than or equal to 0.5 cm; when the dezincified steel fiber is immersed in an electrolyte solution containing a chelating agent, the stacking thickness of the dezincified steel fiber is less than or equal to 0.5 cm; when the stainless steel fiber is immersed in an electrolyte solution containing a chelating agent, the stacking thickness of the stainless steel fiber is less than or equal to 2 cm.

[0022] In some embodiments of the present invention, the electrolyte solution containing a chelating agent is prepared from sodium chloride, a solvent and disodium ethylenediaminetetraacetate; the mass ratio of the sodium chloride to the solvent is (1.5-5):100, preferably 3:100; the solvent is water; in the electrolyte solution containing a chelating agent, the concentration of disodium ethylenediaminetetraacetate (EDTA-2Na) is 0.05-0.2 mol / L, preferably 0.1-0.2 mol / L, and more preferably 0.1 mol / L.

[0023] In the present invention, if the sodium chloride ratio is too high, the steel fiber will be severely corroded, and the residual chloride ions are difficult to clean. If the sodium chloride ratio is too low, the speed of the electrochemical reaction (the speed of the chelating reaction) will decrease.

[0024] In some embodiments of the present invention, after the chelating modification is completed, the method further includes the steps of washing and drying the chelating modified steel fiber.

[0025] In some embodiments of the present invention, the drying method is natural air drying at 10-20° C. The present invention adopts low-temperature air drying to reduce surface corrosion of the modified steel fiber.

[0026] The principle of the present invention is as follows:

[0027] Chelating agents are a class of compounds with multiple coordination groups that can form stable complexes with metal ions. This complex can change the activity, stability and solubility of metal ions, thereby accelerating the electrochemical reaction of steel fibers in electrolyte solutions. Compared with traditional EDTA and IDS chelating agents, EDTA-2Na selected in the present invention has higher solubility in water, stronger adsorption capacity for zinc, copper and iron ions, and is more affordable.

[0028] For copper-plated steel fibers: the present invention immerses the copper-plated steel fibers in an alkaline solution, and corrodes and peels off the surface brass through an electrochemical reaction, so that the original rough surface of the steel fiber is exposed, and further dezincification chelation composite modification can be performed, that is, the electrochemical reaction and the chelation effect of the chelating agent on metal ions are utilized to further corrode the surface of the dezincified steel fiber, making the surface of the steel fiber rougher, thereby further improving the interface bonding performance between the steel fiber and the UHPC matrix.

[0029] For stainless steel fiber: the present invention directly immerses the stainless steel fiber in an electrolyte solution containing a chelating agent for modification, that is, utilizes the electrochemical reaction and the chelating effect of the chelating agent on metal ions to corrode the surface of the stainless steel fiber and roughen the surface of the stainless steel fiber.

[0030] The present invention discloses the following technical effects:

[0031] The method provided by the invention is simple, efficient, low-cost, environmentally friendly and pollution-free, and can be applied to large-scale steel fiber surface treatment.

[0032] The method provided by the present invention effectively improves the roughness of the steel fiber surface, improves the interface bonding performance between the steel fiber and the concrete matrix, thereby improving the tensile and flexural strength and fracture toughness of the prepared UHPC. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. Considering that the two diameters of copper-plated steel fibers in the embodiment are produced by the same company and have similar surface morphologies, only the surface scanning electron microscope image of the copper-plated steel fiber with a diameter of 0.2 mm is shown.

[0034] Figure 1 It is a schematic diagram of the dezincification and dezincification chelation modification process of copper-plated steel fiber in the present invention;

[0035] Figure 2 Comparison of single fiber drawing results of copper-plated steel fiber of size 1 in Examples 1-4;

[0036] Figure 3 Comparison of single fiber drawing results of copper-plated steel fibers of size 2 in Examples 1-4;

[0037] Figure 4 This is a scanning electron microscope image of the surface of the unmodified steel fiber of size 1 in Example 1;

[0038] Figure 5 This is a scanning electron microscope image of the surface of the dezincified modified steel fiber of size 1 in Example 1;

[0039] Figure 6 This is a scanning electron microscope image of the surface of a steel fiber of size 1 that has been dezincified and chelated for 3 hours in Example 2;

[0040] Figure 7 This is a scanning electron microscope image of the surface of a steel fiber of size 1 that has been dezincified and chelated for 6 hours in Example 3;

[0041] Figure 8 This is a scanning electron microscope image of the surface of a size 1 steel fiber in Example 4 after dezincification and chelation for 9 hours. DETAILED DESCRIPTION

[0042] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0043] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0044] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0045] In the description of the present invention, it should be understood that the terms "longitudinal", "lateral", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside" and "outside" etc., indicating orientations or positional relationships, are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.

[0046] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0047] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0048] In order to better understand the present invention, the following examples are combined to further illustrate the content of the present invention, but the content of the present invention is not limited to the following examples. Figure 1 .

[0049] The copper-plated steel fiber used in the embodiment is a straight copper-plated steel fiber. The straight copper-plated steel fiber has two sizes. Size 1 is: length 20 mm, diameter 0.2 mm, aspect ratio 100, and tensile strength 2580 MPa; Size 2 is: length 25 mm, diameter 0.3 mm, aspect ratio 83.3, and tensile strength 2200 MPa.

[0050] The raw materials for preparing the ultra-high performance concrete mortar in the embodiment are: 950 parts of PO52.5 cement, 200 parts of silica fume with a purity of more than 90%, 525 parts of 16-26 mesh machine-made sand / quartz sand, 315 parts of 26-40 mesh machine-made sand / quartz sand, 210 parts of 40-70 mesh machine-made sand / quartz sand, 20 parts of water reducer, and 210 parts of water.

[0051] Example 1

[0052] A method for improving the interface performance between steel fiber and matrix in UHPC, the steps are as follows:

[0053] Step 1. Preparation of saturated calcium hydroxide solution: Take 20g of calcium hydroxide powder and stir and disperse it in 1L of clean water.

[0054] Step 2. Evenly disperse 20 g of copper-plated steel fiber in a container filled with saturated calcium hydroxide solution and soak it for 7 days. Finally, remove it, wash it, and air-dry it at low temperature to obtain dezincified steel fiber.

[0055] The prepared dezincified steel fiber was embedded in ultra-high performance concrete mortar with an embedding length of 6 mm and an embedding angle of 0°. After standard curing for 48 hours, it was cured in 90°C hot water for 72 hours, and a single fiber pull-out test was performed to measure the pull-out adhesion and pull-out energy of a single fiber. The ultimate adhesion and pull-out energy of the unmodified copper-plated steel fiber (size 1) were 33.92N and 119.26N·mm, respectively, and the ultimate adhesion and pull-out energy of the dezincified fiber (size 1) were 47.64N and 224.65N·mm, respectively. The ultimate adhesion and pull-out energy of the unmodified copper-plated steel fiber (size 2) were 63.5N and 193.24N·mm, respectively, and the ultimate adhesion and pull-out energy of the dezincified fiber (size 2) were 94.99N and 332.55N·mm, respectively.

[0056] Example 2

[0057] A method for improving the interface performance between steel fiber and matrix in UHPC, the steps are as follows:

[0058] Step 1. Preparation of an electrolyte solution containing a chelating agent: weigh 30 g of sodium chloride and 1000 g of deionized water and mix them evenly, then add 37.4 g of EDTA-2Na (disodium ethylenediaminetetraacetic acid) and stir evenly.

[0059] Step 2. Weigh 50 grams of the dezincified steel fiber obtained in Example 1 and disperse it in an electrolyte solution containing a chelating agent, soak it for 3 hours, remove it, wash it, and air-dry it at 10°C.

[0060] The dezincified fiber after chelation treatment for 3 hours was buried in ultra-high performance concrete mortar with an embezzlement length of 6 mm and an embezzlement angle of 0°. After standard curing for 48 hours, it was cured in 90-degree hot water for 72 hours, and a single fiber pull-out test was performed to measure the pull-out adhesion and pull-out energy of a single fiber. The ultimate adhesion and pull-out energy of the unmodified copper-plated steel fiber (size 1) were 33.92 N and 119.26 N mm, respectively, and the ultimate adhesion and pull-out energy of the dezincified fiber (size 1) after chelation treatment for 3 hours were 38.81 N and 131.66 N mm, respectively. The ultimate adhesion and pull-out energy of the unmodified copper-plated steel fiber (size 2) were 63.5 N and 193.24 N mm, respectively, and the ultimate adhesion and pull-out energy of the dezincified fiber (size 2) after chelation treatment for 3 hours were 76.4 N and 227.9 N mm, respectively.

[0061] Example 3

[0062] A technology and method for improving the performance of the interface between steel fiber and matrix in UHPC, the steps are as follows:

[0063] Step 1. Preparation of an electrolyte solution containing a chelating agent: Weigh 30 g of sodium chloride and 1000 g of deionized water and mix them evenly, then add 37.4 g of EDTA-2Na (disodium ethylenediaminetetraacetic acid) and stir evenly.

[0064] Step 2. Weigh 50 grams of the dezincified steel fiber obtained in Example 1 and disperse it in an electrolyte solution containing a chelating agent, soak it for 6 hours, remove it, wash it, and air-dry it at 15°C.

[0065] The dezincified fiber treated with chelation for 6 hours was buried in ultra-high performance concrete mortar with an embezzlement length of 6 mm and an embezzlement angle of 0°. After standard curing for 48 hours, it was cured with 90-degree hot water for 72 hours, and a single fiber pull-out test was performed to measure the pull-out adhesion and pull-out energy of a single fiber. The ultimate adhesion and pull-out energy of the unmodified copper-plated steel fiber (size 1) were 33.92 N and 119.26 N mm, respectively, and the ultimate adhesion and pull-out energy of the dezincified fiber (size 1) treated with chelation for 6 hours were 47.65 N and 127.93 N mm, respectively. The ultimate adhesion and pull-out energy of the unmodified copper-plated steel fiber (size 2) were 63.5 N and 193.24 N mm, respectively, and the ultimate adhesion and pull-out energy of the dezincified fiber (size 2) treated with chelation for 6 hours were 77.53 N and 264.6 N mm, respectively.

[0066] Example 4

[0067] A method for improving the interface performance between steel fiber and matrix in UHPC, the steps are as follows:

[0068] Step 1. Preparation of an electrolyte solution containing a chelating agent: weigh 30 g of sodium chloride and 1000 g of deionized water and mix them evenly, then add 37.4 g of EDTA-2Na (disodium ethylenediaminetetraacetic acid) and stir evenly.

[0069] Step 2. Weigh 50 grams of the dezincified steel fiber obtained in Example 1 and disperse it in an electrolyte solution containing a chelating agent, soak it for 9 hours, remove it, wash it, and air-dry it at 15°C.

[0070] The dezincified fiber treated with chelation for 9 hours was buried in ultra-high performance concrete mortar with an embezzlement length of 6 mm and an embezzlement angle of 0°. After standard curing for 48 hours, it was cured with 90-degree hot water for 72 hours, and a single fiber pull-out test was performed to measure the pull-out adhesion and pull-out energy of a single fiber. The ultimate adhesion and pull-out energy of the unmodified copper-plated steel fiber (size 1) were 33.92 N and 119.26 N·mm, respectively, and the ultimate adhesion and pull-out energy of the dezincified fiber (size 1) treated with chelation for 9 hours were 52.93 N and 183.32 N·mm, respectively. The ultimate adhesion and pull-out energy of the unmodified copper-plated steel fiber (size 2) were 63.5 N and 193.24 N·mm, respectively, and the ultimate adhesion and pull-out energy of the dezincified fiber (size 2) treated with chelation for 9 hours were 102.73 N and 325.11 N·mm, respectively.

[0071] The statistical results of the single fiber drawing test results of the straight copper-plated steel fibers of size 1 and size 2 in Examples 1-4 are shown in Tables 1 and 2, and the single fiber drawing results are compared in Tables 1 and 2. Figure 2 , Figure 3 .

[0072] Table 1 Single fiber pulling test results of straight copper-coated steel fiber (size 1)

[0073]

[0074] Table 2 Single fiber pulling test results of straight copper-coated steel fiber (size 2)

[0075]

[0076] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for improving the interface performance between steel fiber and matrix in UHPC, characterized in that: There are three methods involved; Method 1: soaking the copper-plated steel fiber in an alkaline solution for dezincification treatment, and then washing and drying the copper-plated steel fiber after the dezincification treatment in sequence to obtain the dezincified steel fiber; Method 2: soaking the dezincified steel fiber described in method 1 in an electrolyte solution containing a chelating agent for chelation modification; Method 3: Soak the stainless steel fiber in an electrolyte solution containing a chelating agent for chelation modification; The alkaline solution is a calcium hydroxide solution, a sodium hydroxide solution or a potassium hydroxide solution; The chelating agent is disodium ethylenediaminetetraacetate.

2. The method for improving the interface performance between steel fiber and matrix in UHPC according to claim 1, characterized in that: The concentrations of the sodium hydroxide solution and the potassium hydroxide solution are both 0.05-0.1 mol / L, and the calcium hydroxide solution is prepared by mixing calcium hydroxide and water in a mass ratio of (0.5-2):

100.

3. The method for improving the interface performance between steel fiber and matrix in UHPC according to claim 1, characterized in that: The mass ratio of the copper-plated steel fiber to the alkaline solution is 1:(30-100); the mass ratio of the dezincified steel fiber to the electrolyte solution containing a chelating agent is 1:(10-50); the mass ratio of the stainless steel fiber to the electrolyte solution containing a chelating agent is 1:(10-50).

4. The method for improving the interface performance between steel fiber and matrix in UHPC according to claim 1, characterized in that: When the copper-plated steel fiber is immersed in an alkaline solution for dezincification treatment, the immersion time is 5-10 days; when the dezincified steel fiber is immersed in an electrolyte solution containing a chelating agent for chelation modification, the immersion time is 3-9 hours; when the stainless steel fiber is immersed in an electrolyte solution containing a chelating agent for chelation modification, the immersion time is 3-9 hours.

5. The method for improving the interface performance between steel fiber and matrix in UHPC according to claim 1, characterized in that: The electrolyte solution containing the chelating agent is prepared from sodium chloride, a solvent and disodium ethylenediaminetetraacetate; the mass ratio of the sodium chloride to the solvent is (1.5-5):100; in the electrolyte solution containing the chelating agent, the concentration of disodium ethylenediaminetetraacetate is 0.05-0.2 mol / L.

6. The method for improving the interface performance between steel fiber and matrix in UHPC according to claim 1, characterized in that: After the chelating modification is completed, the method further includes the steps of washing and drying the chelating modified steel fiber.

7. The method for improving the interface performance between steel fiber and matrix in UHPC according to claim 6, characterized in that: The drying method is natural air drying at 10-20°C.